Beliefs about Genetic Influences on Eating Behaviors: Characteristics and Associations with Weight Management Confidence - Persky, Susan (Eat Behav, 2017)
INTRODUCTION: The development of precision approaches for customized health interventions is a promising application of genomic discovery. To optimize such weight management interventions, target audiences will need to be engaged in research and implementation efforts. Investigation into approaches that engage these audiences will be required to ensure that genomic information, particularly with respect to genomic influences on endophenotypes like eating behavior, is understood and accepted, and not associated with unintended adverse outcomes. We took steps to characterize healthy individuals’ beliefs about genetic influences on eating behavior. METHODS: Data were collected via online survey from 261 participants selected at random from a database. RESULTS: Respondents infrequently spontaneously identified eating behavior-related factors as running in families. However, those who perceived themselves as overweight and perceived a family history of overweight were more likely to attribute eating behavior to genetics on closed-ended assessments, β=.252, p=.039. Genetic attributions for eating behaviors were associated with lower confidence in ability to control eating and weight, β=−.119, p=.035. CONCLUSIONS: These exploratory findings shed light on beliefs about genetic influences on eating, a behavioral trait (rather than a disease). This investigation can inform future health intervention efforts.